KUFR DALAM PERSPEKTIF HADIS - Abidin, Zainal (State Institute of Islamic Studies (IAIN) Palu, 2008)
Kufr is often considered an antithesis of imân. In the mean time, imân is the fundamental part of Islamic teaching. Nevertheless, as far as the sources of Islamic teaching are concerned, the term kufr cannot necessarily be grasped as disbelief in Allah (God). In some hadîths (the prophet’s traditions), we find some terms of kufr that do not indicate disbelief in Allâh at all. Even, some merely indicate disobedience of the Muslims in performing their Islamic teachings, such as performing salât. Based on this, this article deals with kufr from the hadîth perspective.Kata Kunci : kufr, perspektif hadis, dosa besar